Green Synthesis of ZnO Nanoparticles using Abelmoschus esculenthus L. Fruit Extract: Antioxidant, Photoprotective, Anti-inflammatory, and Antibacterial Studies - Christina Astutiningsih; Tias Eka Rahmawati; Nanik Astutik Rahman; Meri Meri (Pandawa Institute, 2024)
Nanoparticles are extensively studied for their promising biological properties. In this study, the fruit extract of Abelmoschus esculenthus L. was used as a chelating agent for the synthesis of zinc oxide nanoparticles (ZnOPs-AE) using a zinc acetate solution. The prepared ZnOPs-AE were identified and characterized using UV-vis spectroscopy, Fourier-transformed infrared spectroscopy (FTIR), particle size analyzer (PSA), scanning electron microscopy (SEM), and energy dispersive spectrum (EDS). The green synthesized ZnOPs-AE were evaluated for their antioxidant, photoprotective, anti-inflammatory, and antibacterial activities. The synthesized nanoparticles showed an intensity peak at 370 nm in the UV-vis spectrum. The FTIR result shows the presence of O-H, C=O, C-O, C-OH, and C=C chelating functional groups on the surface of nanoparticles. The size of ZnOPs-AE was determined using a PSA with particle size distribution of 102.2 nm. The ZnOPs-AE were shown to be spherical by SEM analysis and composition was 82.11% and 14.79% for Zn and O, respectively. The antioxidant properties of ZnOPs-AE showed significant antioxidant potential in DPPH, ABTS, and FRAP assays compared to the quercetin standard. The photoprotection activity test showed a SPF value of 19.63, the percentage of erythema transmission was 5.98%, and the percentage of pigmentation transmission was 5.62%. The ZnOPs-AE showed good anti-inflammatory with the synthesized nanoparticle performing activity between positive control and the fruit extract of Abelmoschus esculenthus L. Also, the ZnOPs-AE exhibited good antibacterial activity against Staphylococcus aureus (20.78 mm) and Pseudomonas aeruginosae (11.13 mm). Overall, the results highlight the effectiveness and potential of ZnOPs-AE for biological application.